2016
DOI: 10.1093/glycob/cww064
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of hyaluronic acid formation sensitizes chronic myelogenous leukemia to treatment with doxorubicin

Abstract: In the current study we examined the ability of 4-methylumbelliferone (4-MU), which can inhibit hyaluronic acid synthesis, to sensitize K562 chronic myelogenous leukemia (CML) cells to doxorubicin therapy. Exposure of K562 cells to doxorubicin led to increased hyaluronic acid synthase (HAS) gene expression and increased levels of cell surface hyaluronic acid. Furthermore, exposure of K562 cells to exogenous HA caused resistance to doxorubicin-induced cell death. The combination of low dose 4-MU and doxorubicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…HAS2 and HAS3 were similarly increased in OV-90 CBP cells that acquired CBP resistance compared to parental OV-90 cells. Recent studies have also shown that leukemic cell lines with increased HA production resist chemotherapy [23,24]. Together, these findings support the concept that HA plays an important role in the development of acquired chemotherapy resistance.…”
Section: Discussionsupporting
confidence: 66%
“…HAS2 and HAS3 were similarly increased in OV-90 CBP cells that acquired CBP resistance compared to parental OV-90 cells. Recent studies have also shown that leukemic cell lines with increased HA production resist chemotherapy [23,24]. Together, these findings support the concept that HA plays an important role in the development of acquired chemotherapy resistance.…”
Section: Discussionsupporting
confidence: 66%
“…The antitumor effect results from reduced CD44 activation that lowers PI3K signaling and AKT and ERK phosphorylation (Kundu et al, 2013;Lompardia et al, 2017). Others have shown that 4-MU increases p38 activation and caspase-3, caspase-9, and PARP cleavage, explaining not only the apoptotic effect but might also indicate an increased sensitivity toward cytotoxic stress (Lokeshwar et al, 2010;Uchakina et al, 2016). Importantly, these proapoptotic effects can be rescued by HA addition to cultured cells, demonstrating that these are direct results of reduction in HAS activity and not off-target effects.…”
Section: Targeting Hyaluronan Synthesismentioning
confidence: 99%
“…These authors also showed the proapoptotic effect of 4-MU in vivo, where treatment of tumorbearing mice with 4-MU significantly reduced tumor growth through the induction of apoptosis (62). These results, together with those of other studies, determine the role of 4-MU as a molecule that favors the response of CML to chemotherapy (63,64) and suggest that 4-MU is an excellent candidate for use in combination with conventional therapeutic strategies.…”
Section: Chronic Myeloid Leukemiasmentioning
confidence: 61%
“…Similarly, different studies have proposed 4-MU as a candidate molecule for co-adjuvant treatments for CML. Uchakina et al showed that 4-MU sensitizes K562 cells to doxorubicin treatment, by inhibiting HA synthesis and increasing apoptosis rates through p38 activation and PARP cleavage (63). Lompardıá et al found similar results when combining 4-MU treatment with the chemotherapeutic agent vincristine on K562 and K562 vincristine-resistant cells (Kv562) (64).…”
Section: -Mu Treatment As a New Strategy Of Co-adjuvant Drug On Conventional Antineoplastic Therapiesmentioning
confidence: 96%